1998
DOI: 10.1159/000027324
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Retinitis pigmentosa: Clinical and Electrophysiological Report of Four Cases

Abstract: Unilateral retinitis pigmentosa (URP) is a rare tapetoretinal dystrophy affecting only one eye. The François and Verriest criteria are necessary to make a correct diagnosis of URP: exclude all infective etiologies, check that the clinical signs of retinitis are present in the affected eye and ensure the total absence of any signs or symptoms of retinitis pigmentosa in the fellow eye. The standard electroretinogram and standard electro-oculogram are very useful for the correct diagnosis. Other pigmentary retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
(7 reference statements)
3
12
0
2
Order By: Relevance
“…The observation that a genetic diagnosis could be reached in only two cases is consistent with previous studies of atypical that have suggested a high incidence of acquired disease (Joseph ; Spadea et al. ; Chen et al. ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observation that a genetic diagnosis could be reached in only two cases is consistent with previous studies of atypical that have suggested a high incidence of acquired disease (Joseph ; Spadea et al. ; Chen et al. ).…”
Section: Discussionsupporting
confidence: 91%
“…There was difficulty in establishing an aetiology in many patients but, importantly, a family history suggesting a heritable cause was present in only two of the patients. The observation that a genetic diagnosis could be reached in only two cases is consistent with previous studies of atypical that have suggested a high incidence of acquired disease (Joseph 1951;Spadea et al 1998;Chen et al 2006). Detailed electrophysiological testing showed generalized retinal dysfunction in the eye with pigmentary changes that varied in severity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unilateral retinitis pigmentosa (URP) is a rare degeneration of the photoreceptors involving retinitis pigmentosa-like changes in one eye with the other eye completely unaffected [3]. The criteria for diagnosis of URP are:…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, nesses casos, o ERG já apresenta alterações em ambos os olhos desde o início da doença (6) . O tempo ideal de acompanhamento do paciente para o diagnostico de RPU ainda é controverso.…”
Section: A B Discussãounclassified